An apolitical generation: why is the young generation of Lithuania is not interested in politics? - Diržinskaitė, Aušrinė (Politologija, 2018)
[full article and abstract in Lithuanian; abstract in English] In the recent years, consolidated democracies have faced a great decline in citizens’ participation and interest in political life. The latest researches show that young people are especially disengaged and alien to political life. Moreover, Lithuania seems to have the greatest number of young people who are not interested in politics in the “so-called” developed world (OECD countries and candidates) and has the highest gap between the general and the youth interest in politics. Therefore, this article analyzes what are the reasons for the disinterest in politics of the youth in Lithuania. Contemporary theories and empirical researches suggest rather different answers to the question. In particular, it is said that youths’ interest in politics can be determined by three categories of factors: socioeconomic/sociodemographic (income, wellbeing, education, race and gender), psychological (political efficacy: self-confidence as internal political efficacy and trust in political system as external political efficacy) as well as socializing factors (discussions with family and friends, media, volunteering). In order to find why Lithuania has such a high level of youth disinterest in politics, the analysis is performed on an individual level. Logistic regression analysis shows that the most relevant determinants for the youth interest in politics in Lithuania are a greater usage of media, accompanied with more frequent discussions with family and friends, a higher trust in the parliament as well as a higher level of education. Yet, the greatest determinant of whether a young person will be interested in politics are the elections; i.e., data from the year 2016 signalizes a much greater youth interest in politics compared to the 2012, thus inviting to analyze more deeply the existing differences between the two elections. To check if the variables had proved significant on the individual level, bore any semblance on the country level and explained the exception of Lithuania, an aggregate analysis was conducted. Correlations were found between the level of youth disinterest in politics and income per capita, trust in the national government, discussions with friends and the usage of media. Lithuania, the Czech Republic, Hungary and Slovakia appear to be in one group based on most of the analyzed criteria. Though altogether these factors seem to be pretty good determinants, the Lithuanian case is, however, not fully explained by them – a regression model is unable to predict almost one fifth of the young people that are disinterested in politics in Lithuania. Thus, the usual suspects do not explain this phenomenon fully, and particular countries should be explored more deeply.